Meningkatkan Kompetensi Guru Dalam Mengajar Melalui Kegiatan Supervisi Akademik Dengan Teknik Individual - Roslindah Roslindah (Universitas Negeri Makassar, 2019)
The problem in research is the low competence of teachers in teaching in the Kindergarten Areas. State of Trustees of Ajangale Subdistrict of Bone Regency 2018/2019 Academic Year. The aim is to improve teacher competence in teaching. The research subjects are classroom teachers in the kindergarten-assisted areas. State of Trustees of Ajangale Subdistrict of Bone Regency in 2018/2019 Academic Year. which amounted to 6 teachers with non-bachelor (S-1) education backgrounds. Data collection techniques using observation and documentation techniques. Data analysis uses descriptive qualitative techniques. The results showed that increasing teacher competency in teaching was assessed through 4 aspects of assessment, namely planning, implementation, assessment and supervision of the learning process showed a significant increase in each cycle. Average results of the assessment of 4 aspects of teacher competency assessment in teaching in each cycle can be explained that in the initial conditions of 56.18 included in the criteria (C), in the second cycle 74.20 included in the criteria (C) and in the last cycle of 95.15 and included in the value criteria (SB). The conclusion is that the implementation of academic supervision with individual techniques is supported by the implementation of supervision of classroom visits proven to be able to improve the competence of teachers in the Kindergarten Areas. State of Trustees of Ajangale Subdistrict of Bone Regency in 2018/2019 Academic Year.